Learning From the Perspective of Islamic Educational Psychology in the Age of Digital Distractions - Lisa Mutia; Desi Warni; Alfi Rahmi (Journal of Education and Teacher Training Innovation, 2026)
The digital age has brought fundamental changes to the educational landscape; however, it has also given rise to the phenomenon of digital distraction, which has a serious impact on the quality of student learning. Uncontrolled smartphone use, social media addiction, and dependence on short-form digital content have been shown to reduce students’ concentration, motivation to learn, and psychological well-being. Amid these challenges, Islamic Educational Psychology offers a holistic conceptual framework for understanding and addressing these issues. This study aims to examine learning concepts from the perspective of Islamic Educational Psychology as a response to the increasingly widespread digital distractions. The method employed is library research using a content analysis approach on literature sources, comprising international and national articles. The findings indicate that the concepts of fitrah, self-control, and Islamic epistemology provide a solid foundation for developing learning strategies resilient to digital distractions. Islamic Educational Psychology is not merely reactive but offers preventive solutions grounded in spiritual and moral values. This study contributes to the development of contemporary Islamic educational theory that is adaptive to the challenges of the digital age.